FRI0575 BIOMARKER ANALYSIS FROM THE RISE-SSC STUDY OF RIOCIGUAT IN EARLY DIFFUSE CUTANEOUS SYSTEMIC SCLEROSIS (DCSSC). (2nd June 2020) - Distler, O.; Kramer, F.; Höfler, J.; Ghadessi, M.; Sandner, P.; Allanore, Y.; Denton, C.; Kuwana, M.; Matucci-Cerinic, M.; Pope, J.; Atsumi, T.; Bečvář, R.; et al.
Abstract : Background: RISE-SSc (NCT02283762 ) was a multicenter, double-blind, Phase IIb study of riociguat in early dcSSc. Primary endpoint was change in mRSS from baseline to Wk 52. Objectives: Exploratory, descriptive analyses of riociguat target engagement and effects on disease biomarkers in RISE-SSc and their relationship with effects on the primary endpoint. All biomarker p-values are for information only. Methods: Pts with dcSSc (duration ≤18 mo; modified Rodnan skin score [mRSS] 10–22 units) were randomized to riociguat 0.5−2.5 mg tid (n=60) or placebo (n=61). Biomarkers of target engagement (cGMP), inflammation and/or vascular/endothelial function (e.g. high-sensitivity C-reactive protein [hsCRP], soluble platelet endothelial cell adhesion molecule 1 [sPECAM-1], soluble E-selectin, chemokine ligand 4 [CXCL-4]), and fibrosis (e.g. alpha-smooth muscle cell actin [alphaSMA], pro-collagen mRNA expression) were measured in plasma, serum, and skin biopsies at baseline and Wk 14. Results: Mean±SD change from baseline in mRSS was –2.09±5.66 (n=57) with riociguat and –0.77±8.24 (n=52) with placebo (p=0.08). From baseline to Wk 14, plasma cGMP rose by mean (SD) 94% (78%) (n=52) with riociguat and 10% (39%) (n=52) with placebo (nominal p<0.001). Serum sPECAM-1 and CXCL-4 fell with riociguat vs placebo; changes in hsCRP or E-selectin differed little between groups (Fig 1 ). Pts with higher baseline sPECAM-1 showed larger mRSS reductions with riociguat vs placebo than pts with lower levels (nominal interaction p=0.004). In baseline skin biopsies, 34% and 31% of pts in the riociguat and placebo groups, respectively, had no alphaSMA-positive cells; other pts had +ve cells (alphaSMA counts 0.1–99.5, median 2.5), a potential indicator of higher disease activity. Pts with +ve baseline alphaSMA counts showed a reduction of mRSS with riociguat vs placebo (Fig 2 ). Skin collagen mRNA expression biomarkers in skin biopsies showed no differences between groups. Conclusion: Primary study endpoint (change in mRSS) was not met. Plasma cGMP rose with riociguat, confirming engagement with the NO-sGC-cGMP pathway. Serum sPECAM-1 (marker of endothelial activation) and CXCL-4 (marker of progressive SSc) fell with riociguat; hsCRP and E-selectin did not. Some serum and skin biomarkers of higher disease activity at baseline were associated with a greater effect of riociguat on skin fibrosis. Acknowledgments: RISE-SSc was jointly funded by Bayer AG and Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure of Interests: Oliver Distler Grant/research support from: Grants/Research support from Actelion, Bayer, Boehringer Ingelheim, Competitive Drug Development International Ltd. and Mitsubishi Tanabe; he also holds the issued Patent on mir-29 for the treatment of systemic sclerosis (US8247389, EP2331143)., Consultant of: Consultancy fees from Actelion, Acceleron Pharma, AnaMar, Bayer, Baecon Discovery, Blade Therapeutics, Boehringer, CSL Behring, Catenion, ChemomAb, Curzion Pharmaceuticals, Ergonex, Galapagos NV, GSK, Glenmark Pharmaceuticals, Inventiva, Italfarmaco, iQvia, medac, Medscape, Mitsubishi Tanabe Pharma, MSD, Roche, Sanofi and UCB, Speakers bureau: Speaker fees from Actelion, Bayer, Boehringer Ingelheim, Medscape, Pfizer and Roche, Frank Kramer Employee of: Bayer AG, Josef Höfler Employee of: Josef Höfler is an employee of Staburo GmbH, Munich, Germany, contracted by Bayer AG to perform the biomarker analyses, Mercedeh Ghadessi Employee of: Bayer AG, Peter Sandner Employee of: Bayer AG, Yannick Allanore Grant/research support from: BMS, Inventiva, Roche, Sanofi, Consultant of: Actelion, Bayer AG, BMS, BI, Christopher Denton Grant/research support from: GlaxoSmithKline, CSL Behring, and Inventiva, Consultant of: Medscape, Roche-Genentech, Actelion, GlaxoSmithKline, Sanofi Aventis, Inventiva, CSL Behring, Boehringer Ingelheim, Corbus Pharmaceuticals, Acceleron, Curzion and Bayer, Masataka Kuwana Grant/research support from: Acetelion, Consultant of: Acetelion, Bayer, Chugai, Corbus Pharmaceuticals, CSL Behring and Reata Pharmaceuticals. He was a member of the SENSCIS trial Steering Committee (Boehringer Ingelheim), Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Bristol-Myers Squibb, Speakers bureau: Acetelion, Lilly, Boehringer Ingelheim, Janet Pope Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lilly & Company, Merck, Roche, Seattle Genetics, UCB, Consultant of: AbbVie, Actelion, Amgen, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Eicos Sciences, Eli Lilly & Company, Emerald, Gilead Sciences, Inc., Janssen, Merck, Novartis, Pfizer, Roche, Sandoz, Sanofi, UCB, Speakers bureau: UCB, Tatsuya Atsumi Grant/research support from: Eli Lily Japan K.K., Alexion Pharmaceuticals, Inc., Bristol-Myers Squibb Co., AbbVie Inc., Daiichi Sankyo Co., Ltd., Pfizer Inc., Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Astellas Pharma Inc., Consultant of: Gilead Sciences, Inc., Eli Lilly Japan K.K., UCB Japan Co. Ltd., AbbVie Inc., Daiichi Sankyo Co., Ltd., Pfizer Inc., Chugai Pharmaceutical Co., Ltd., Speakers bureau: Eli Lilly Japan K.K., UCB Japan Co. Ltd., Bristol-Myers Squibb Co., AbbVie Inc., Eisai Co. Ltd., Otsuka Pharmaceutical Co., Ltd., Daiichi Sankyo Co., Ltd., Pfizer Inc., Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Takeda Pharmaceutical Co., Ltd., Astellas Pharma Inc., Radim Bečvář Consultant of: Actelion, Roche, László Czirják Consultant of: Actelion, BI, Roche-Genentech, Lilly, Medac, Novartis, Pfizer, Bayer AG, Ellen De Langhe Consultant of: member of advisory board for Boehringer, Eric Hachlla: None declared, Tomonori Ishii: None declared, Osamu Ishikawa: None declared, Sindhu Johnson Grant/research support from: Boehringer Ingelheim, Corbus Pharmaceuticals, GlaxoSmithKline, Roche, Merck, Bayer, Consultant of: Boehringer Ingelheim, Ikaria, Kaisa Laapas Employee of: Partly in-sourced to Bayer, Valeria Riccieri: None declared, Elena Schiopu: None declared, Richard Silver: None declared, Vanessa Smith Grant/research support from: The affiliated company received grants from Research Foundation - Flanders (FWO), Belgian Fund for Scientific Research in Rheumatic diseases (FWRO), Boehringer Ingelheim Pharma GmbH & Co and Janssen-Cilag NV, Consultant of: Boehringer-Ingelheim Pharma GmbH & Co, Speakers bureau: Actelion Pharmaceuticals Ltd, Boehringer-Ingelheim Pharma GmbH & Co and UCB Biopharma Sprl, Chiara Stagnaro: None declared, Viginia Steen Grant/research support from: The associated affiliation has received grants/research from Boehringer Ingelheim, Corbus Pharmaceuticals, CSL Behring, Eicos, Galapagos, Immune Tolerance Network, Reata, Consultant of: Virginia Steen has acted as a consultant for Boehringer Ingelheim, Corbus, CSL Behring, Eicos, Forbius, Wendy Stevens: None declared, Gabriella Szücs: None declared, Marie-Elise Truchetet: None declared, Melanie Wosnitza Employee of: Bayer AG, Dinesh Khanna Shareholder of: Eicos Sciences, Inc./Civi Biopharma, Inc., Grant/research support from: Dr Khanna was supported by NIH/NIAMS K24AR063120, Consultant of: Acceleron, Actelion, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Corbus Pharmaceuticals, Horizon Therapeutic, Galapagos, Roche/Genentech, GlaxoSmithKline, Mitsubishi Tanabe, Sanofi-Aventis/Genzyme, UCB